Blockchain: Applications, Challenges, and Solutions - ZareRavasan, Ahad; Mansouri, Taha; Krčál, Michal; Rouhani, Saeed (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Blockchain applications in different industries are booming, yet there are many unresolved challenges with the mass adoption of the technology. This reprint is an attempt to review some of the applications in different industries and propose solutions to some of the critical challenges in technology adoption.